2012
DOI: 10.1159/000334453
|View full text |Cite
|
Sign up to set email alerts
|

Fas Expression in Renal Cell Carcinoma Accurately Predicts Patient Survival after Radical Nephrectomy

Abstract: Objectives: To investigate Fas, Fas ligand (FasL) and Bcl-2 expression, which are considered to be important apoptotic regulatory factors in renal cell carcinomas (RCCs). Patients and Methods: mRNA quantification and immunohistochemistry allowed for the determination of the expression of these three factors in surgically resected tumors from 82 patients with RCC. The correlation of protein and gene expression with more than 10 years of survival data following nephrectomy (along with clinical and pathologic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Although tumor-associated Fas/Fas ligand expression has been associated with killing of activated T cells (18, 20) and poor survival in RCC (19), our results highlight the potential for immunotherapeutic strategies capable of harnessing this pathway to elicit the removal of Fas-sensitive immunoregulatory cells specifically within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Although tumor-associated Fas/Fas ligand expression has been associated with killing of activated T cells (18, 20) and poor survival in RCC (19), our results highlight the potential for immunotherapeutic strategies capable of harnessing this pathway to elicit the removal of Fas-sensitive immunoregulatory cells specifically within the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 76%
“…Although tumor-derived Fas expression associates with poorer outcome in RCC patients (19), the contributions of tumor-versus leukocyte-associated Fas ligand expression remains incompletely defined, particularly in the context of immunotherapy. By immunohistochemistry, we found that increased Fas ligand expression was associated with advanced stage RCC (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fas-dependent induced apoptosis of activated T cells may be induced by tumoral cells expressing FasL. Such FasL-counterattack was found in non--small cell lung [48] and kidney cancer [49], but it is also characteristic for metastatic colorectal cancer (CRC) [50]. Since CRC was primary tumor site in most patients with liver metastases we suppose that this tumor-lymphocyte relation may have strong connections with decreased number of intratumoral T lymphocytes in LM in comparison to HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with metastatic disease have a median survival of 13 months, the 5-year survival rate is <10% [3]. Poor prognosis and shortened survival rates were recently linked to antiapoptotic events [4] and endoplasmic reticulum stress sensed by glucose-regulated protein 78 (GRP78) [5]. The identification of markers that are linked to renal cell carcinogenesis may improve the detection and diagnosis of RCCs and aid in prognosis as well as in appropriate therapy selection [6].…”
Section: Introductionmentioning
confidence: 99%